Gingival inflammation in the Flemish painter Hendrick ter Brugghen'sUnequal Couplepainting - GÖRKEY, ŞEFİK (SPRINGERNATURE, 2020)
The evaluation of painting in terms of medicine and dentistry is increasingly shared in academic publications. The clear depiction of gingival inflammation seen in the female figure in Hendrick ter Brugghen'sUnequal coupleattracted our attention. It is interesting to note the meticulous transfer of the actual condition of the diseased gingival tissues and the painter's very high observational ability. Although there may be many more examples of observational depictions, we believe that 'dental humanities' will develop by discussing such art works.
Keywords: ART